Information and Causality: Mathematical Reflections on Cancer Biology - Longo, Giuseppe (Organisms. Journal of Biological Sciences, 2018)
Theorizing and measuring radically change in physics when using discrete vs. continuous mathematical spaces. In the 20th century, Quantum and Information Theories brought into the limelight the use of discrete observables and parameters (energy states, spin-up and down, 0 and 1 …). In these theories, the reference to discrete measurable values fundamentally contributed to knowledge construction; it similarly leads to dramatic consequences in life sciences, in particular when biological dynamics are identified with information processing. Following an early debate in physics, we briefly analyze the origin and the nature of the bias thus induced in biology, in particular in relation to the understanding of causality. We show how strong consequences have been derived from vague, common sense notions and then stress their role in cancer biology. Finally, we summarize new theoretical frames that propose different directions as for the organizing principles for biological thinking and experimenting, including in cancer research. Cancer is then viewed as an organismal, tissue-based issue, according to the perspective proposed in (Sonnenschein & Soto, 1999; Baker, 2015).